The performance of marketplace lenders - Roman Kräussl; Zsofia Kräussl; Joshua M. Pollet; Kalle Rinne (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
We analyze the performance of marketplace lending using loan cash flow data from the largest platform, Lending Club. We find substantial risk-adjusted performance of about 40 basis points per month for the entire loan portfolio. Other loan portfolios grouped by risk category have similar risk-adjusted performance. We show that characteristics of the local bank sector for each loan, such as concentration of deposits and the presence of national banks, are related to the performance of loans. Thus, marketplace lending has the potential to finance a growing share of the consumer credit market in the absence of a competitive response from the traditional incumbents.
urn:nbn:de:hebis:30:3-691266
Keywords: G12; G21; 330; Marketplace lending; household finance; financial intermediation; financial innovation; competition